Unstructured proteins of the malaria parasite Plasmodium falciparum as vaccine candidates - Dhanasarnsombut, Kelwalin (The University of Edinburgh, 2013)
Malaria vaccine research has been battling with persistent challenges, including polymorphisms of vaccine antigens, difficulties with production processes, and limited immune protection against the disease. Intrinsically unstructured proteins (IUPs) are a fairly newly classified group of proteins that have no stable 3D structure and are generally heat-resistant. They usually contain low complexity regions and repetitive sequences, both of which are distinct characteristics of the malaria proteome. Surprisingly, some of the vaccine candidates that have been extensively studied were later reported to have unstructured regions, some of which serve as targets of protective immunity. In keeping with their interesting immunological profiles and their unique properties, which are exceptionally beneficial for vaccine production, malarial IUP antigens may be good vaccine candidates. This PhD project has the following aims:- 1) to develop a synthetic unstructured protein antigen based on the Block 2 region of MSP-1, named the MSP-1 hybrid 2) to characterize a novel vaccine antigen derived from the MSP-3.3 protein, namely an IUP region of PF10_0347 gene product, for its potential as a vaccine candidate 3) to develop a second-generation vaccine by combining the MSP-1 hybrid, with two allelic variants of MSP-2, to overcome antigenic polymorphism and strain-specific immune responses 4) to validate protocols for IUP identification from proteins extracted from the malaria parasite. This study showed that 1) MSP-1 hybrid production was scalable, yielding high protein yields with comparable immunological properties to small-scale production. MSP-1 hybrid was shown to be compatible with different adjuvants, and elicited specific antibodies covering the whole range of Block 2 allelic diversities. 2) A novel antigen, MSP-3.3C, an IUP based on the 3’ region of the PF10_0347 gene, was cloned, expressed and purified. Anti-MSP3.3C antibodies showed very strong parasite growth inhibitory effects in vitro. 3) The MSP-multihybrid antigen was expressed using simple techniques, but only at low levels. It contains epitopes from all three parasite antigen components, and is recognized by specific naturally acquired antibodies. 4) an unconventional 2D gel technique was tested as a method of malaria parasite IUP identification. Plans for further validation of this technique were discussed.
Keywords: Malaria vaccine; MSP-1